The ecologo-faunistic and zoogeographical analysis of Hunzah uplands Carabidae - M. Z. Gadjidadaev; G. M. Abdurakhmanov; G. M. Nahibasheva (Юг России: экология, развитие, 2015)
The generic and specific analyses as well as zoogeographical characteristics of Hunzah uplands Carabidae are given in the research